Dose-Dependent Reduction of Replication Elongation Rate by (p)ppGpp in Escherichia coli and Bacillus subtilis - DeNapoli, Jessica (2013)
DNA replication is regulated in response to environmental constraints such as nutrient availability. While much is known about regulation of replication during initiation, little is known about regulation of replication during elongation. In the bacterium Bacillus subtilis, replication elongation is paused upon sudden amino acid starvation by the starvation-inducible nucleotide (p)ppGpp. However, in many bacteria including Escherichia coli, replication elongation is thought to be unregulated by nutritional availability. Here we reveal that the replication elongation rate in E. coli is modestly but significantly reduced upon strong amino acid starvation. This reduction requires (p)ppGpp and is exacerbated in a gppA mutant with increased pppGpp levels. Importantly, high levels of (p)ppGpp, independent of amino acid starvation, are sufficient to inhibit replication elongation even in the absence of transcription. Finally, in both E. coli and B. subtilis, (p)ppGpp inhibits replication elongation in a dose-dependent manner rather than via a switch-like mechanism, although this inhibition is much stronger in B. subtilis. This supports a model where replication elongation rates are regulated by (p)ppGpp to allow rapid and tunable response to multiple abrupt stresses in evolutionarily diverse bacteria.